PENGARUH PERSEPSI DUKUNGAN PERUSAHAAN, SUPERVISOR, KELUARGA DAN TEMAN TERHADAP SELF ESTEEM DAN SELF EFFICACY PARA TENAGA PEMASAR DI PERUSAHAAN PEMBIAYAAN - Damaruci (Sekolah Tinggi Ilmu Ekonomi GICI, 2023)
The aim of this research is to determine the strength of several perceived support variables that influence the self-esteem and self-efficacy of marketers. This research is important, because marketers are the backbone of finance companies. As a marketer, you must have high self-confidence. With the job characteristics of having to deal directly with consumers through the process of persuading, influencing and convincing consumers amidst intense competition from competing companies, a marketer must be able to convince himself before convincing others. Referring to the breathe-edu.co.uk page, self-confidence is formed by self-efficacy and self-esteem. Using a quantitative approach with a survey method of 168 marketers from 42 finance companies in East Jakarta and Bekasi, which were then analyzed using a Structural Equation Model (SEM) approach based on Partial Least Square (PLS). After carrying out a measurement model test (outer model analysis) and a structural model test (inner model analysis), the conclusion is that perception of friends and family support has a significant effect on the self-esteem and self-efficacy of marketers. Perception of supervisor support has a less significant effect on the self-esteem and self-efficacy of marketers. Perception of company support has a significant effect on the self-esteem of marketers but has a less significant effect on the self-efficacy of marketers.